Correlates of the double burden of malnutrition among women: an analysis of cross sectional survey data from sub-Saharan Africa - Catherine Kyobutungi; Dickson Abanimi Amugsi; Zacharie Tsala Dimbuene (BMJ Open)
Objective To investigate the correlates of the double burden of malnutrition (DBM) among women in five sub-Saharan African countries.Design Secondary analysis of Demographic and Health Surveys (DHS). The outcome variable was body mass index (BMI), a measure of DBM. The BMI was classified into underweight (BMI <18.50 kg/m2), normal weight (18.50–24.99 kg/m2), overweight (25.0–29.9 kg/m2) and obesity (≥30.0 kg/m2).Settings Ghana, Nigeria, Kenya, Mozambique and Democratic Republic of Congo (DRC).Subjects Women aged 15–49 years (n=64698).Results Compared with normal weight women, number of years of formal education was associated with the likelihood of being overweight and obese in Ghana, Mozambique and Nigeria, while associated with the likelihood of being underweight in Kenya and Nigeria. Older age was associated with the likelihood of being underweight, overweight and obese in all countries. Positive associations were also observed between living in better-off households and overweight and obesity, while a negative association was observed for underweight. Breastfeeding was associated with less likelihood of underweight in DRC and Nigeria, obesity in DRC and Ghana, overweight in Kenya and overweight and obesity in Mozambique and Nigeria relative to normal weight.Conclusions Our analysis reveals that in all the countries, women who are breastfeeding are less likely to be underweight, overweight and obese. Education, age and household wealth index tend to associate with a higher likelihood of DBM among women. Interventions to address DBM should take into account the variations in the effects of these correlates.